Cardiac-related neonatal collapse presenting to the emergency department: a retrospective cohort study - Jon Lillie; Manson Chon In Kuok; Jennie Lambert; Anitha Janjanam (BMJ Paediatrics Open)
Background To describe the characteristics of cardiac-related neonatal collapses referred to a critical care transport service and evaluate the diagnostic accuracy and management at referral and retrieval.Methods Retrospective cohort analysis of cardiac-related neonatal collapses who were referred to and transferred by a paediatric intensive care retrieval team based in London, UK between 2013 and 2021. Patients with antenatal diagnoses were excluded.Results There were 71 neonates identified of whom 49 (69%) had structural heart defect, 12 (17%) arrhythmia and 10 (14%) with cardiomyopathy/myocarditis. Among structural defects, left ventricular outflow tract (LVOT) obstruction (71%) and mixing of circulation (22%) were the predominant pathologies. Cardiac murmur was absent in 66% of the patients. The referring teams’ diagnostic performance was suboptimal for LVOT obstruction and cardiomyopathy/myocarditis, with 63% and 30% recognised as cardiac cause of collapse at referral. Less than half of neonates with duct-dependent lesions received prostaglandin at referral, which later improved to 97% during retrieval. The number of patients requiring intubation and inotropic support also increased at various time points throughout the patient journey. 98% of patients with structural defects required cardiac interventions at a median of 1 day after admission.Conclusions Structural heart defect, particularly LVOT obstruction, was the leading cause of cardiac-related neonatal collapses. However, a significant portion were initially misdiagnosed leading to delay in prostaglandin administration. Our findings highlight the importance of a high index of suspicion for cardiac pathologies as a cause of neonatal collapse, which is essential for appropriate treatment and timely referral.